2017
DOI: 10.1002/jmv.24980
|View full text |Cite
|
Sign up to set email alerts
|

Changing pattern of prevalence, genetic diversity, and mixed infections of viruses associated with acute gastroenteritis in pediatric patients in New Delhi, India

Abstract: There are very few studies that have assessed multiple viral agents causing Acute-Gastroenteritis (AGE) in India. The present study compared the changing pattern of prevalence and genetic diversity of five enteric viruses associated with acute-diarrhea in Delhi children within a gap of 5 years. Fecal samples were collected from diarrheal children (<4 years) during two winter seasons: year 2009-2010 (n = 59) and year 2014-2015 (n = 85). Samples were individually tested for rotavirus-A, norovirus, astrovirus, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
10
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 45 publications
14
10
1
1
Order By: Relevance
“…There were significantly high rates of infection among children younger than 2 years old, especially those between 6 and 11 months old. These findings are well in agreement with those of previous studies (Subekti et al, 2002; Sowmyanarayanan et al, 2012; Gupta et al, 2018). The lower prevalence in older children could be due to acquired immunity through previous exposures (Velazquez, 2009).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…There were significantly high rates of infection among children younger than 2 years old, especially those between 6 and 11 months old. These findings are well in agreement with those of previous studies (Subekti et al, 2002; Sowmyanarayanan et al, 2012; Gupta et al, 2018). The lower prevalence in older children could be due to acquired immunity through previous exposures (Velazquez, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…Strain diversity occurs over time along with temporal and genetic changes in the viruses (Gupta et al, 2018). The accumulation of knowledge about the features of viral strains may provide insight into what impact the introduction of rotavirus vaccination has on virus epidemiology and circulating genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…While most epidemiological studies on enteric viruses in children identified rotavirus as the first viral cause of acute sporadic gastroenteritis [24,25,26,27,28], we found a higher positivity rate for adenovirus, which could be biased on the fact that positive samples for rotavirus and adenovirus by immunochromatography were excluded from the analyses. Yet, two other recent studies also identified higher prevalence of adenovirus than rotavirus infection among a cohort of children with gastroenteritis using real-time PCR assays [29,30], including one study that focused on the post rotavirus vaccine era [30].…”
Section: Discussioncontrasting
confidence: 70%
“…Therefore, combined characterization of both capsid and polymerase regions is substantial to monitor the new recombinant strains and the new emerging NoV genotype worldwide. GII.1 capsid genotype found in this study has been recently reported in Cameroon [ 48 ], Brazil [ 49 , 50 ], Australia [ 51 ], India [ 52 ], and elsewhere [ 53 55 ]. This genotype is frequently reported from both clinical cases and environmental samples.…”
Section: Discussionsupporting
confidence: 81%
“…(iii) GII.1 capsid genotype found in this study has been recently reported in Cameroon [48], Brazil [49,50], Australia [51], India [52], and elsewhere [53][54][55]. is genotype is frequently reported from both clinical cases and environmental samples.…”
Section: Discussionsupporting
confidence: 74%